Dark river - Escott, Harry 1976- (Arrow Films, 2018)
"Following the death of her father, Alice returns to her home village for the first time in fifteen years, to claim the tenancy to the family farm she believes is rightfully hers. [...]" [arrowfilms.com]
Original: Großbritannien 2017
Special features: Interviews with writer-director Clio Barnard and actors Ruth Wilson, Mark Stanley, Sean Bean and Esmé Creed-Miles ; behind the scenes ; Stills gallery ; original trailer ; reversible sleeve featuring two artwork options
Bildformat 1.85:1
Keywords: Film; DVD-Video